Incidence of Milk Fever on Dairy Cows and Its Risk Factors in Gondar Town, Northwest Ethiopia (International Journal of Natural Sciences, 2013)
The study was conducted on 384 dairy cows in Gondar town during October, 2009 to January, 2010 to determine the prevalence of milk fever and risk factors associated with the disease. Data was collected using regular farm visits, clinical examination of periparturient cows and response to treatment. The overall prevalence of milk fever was 30.2%. Milk fever was significantly associated with milk yield (p